Pengaruh Good Corporate Governance dan Kinerja Keuangan terhadap Financial Distress: Studi Empiris pada Perusahaan Subsektor Jasa Konsumen yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Elsa Fania; Erinos NR (Universitas Negeri Padang, 2023)
This study aims to examine the effect of good corporate governance and financial performance on financial distress. This type of research is causal research with a quantitative approach. The data source used is secondary data from the annual reports of consumer services sub-sector companies listed on the Indonesian stock exchange in 2017-2021. The population in this study is the consumer service sub-sector companies listed on the Indonesian stock exchange in 2017-2021. Purposive sampling technique was used for sampling in order to obtain 105 samples. This study uses logistic regression analysis and paired sample t-test using SPSS 25. The results of logistic regression analysis show that the size of the audit committee and the proportion of independent commissioners have no effect on financial distress, while profitability and liquidity have a negative effect on financial distress. The results of the paired sample t-test show that there are differences financial distress in consumer services sub-sector companies before and after Covid-19.